Cognitive influences on fixational eye movements - Lin, Yen-Chu; Intoy, Janis; Clark, Ashley M.; Rucci, Michele; Victor, Jonathan D. (Current biology, 2023)
We perceive the world based on visual information acquired via oculomotor control,1 an activity intertwined with ongoing cognitive processes.2,3,4 Cognitive influences have been primarily studied in the context of macroscopic movements, like saccades and smooth pursuits. However, our eyes are never still, even during periods of fixation. One of the fixational eye movements, ocular drifts, shifts the stimulus over hundreds of receptors on the retina, a motion that has been argued to enhance the processing of spatial detail by translating spatial into temporal information.5 Despite their apparent randomness, ocular drifts are under neural control.6,7,8 However little is known about the control of drift beyond the brainstem circuitry of the vestibulo-ocular reflex.9,10 Here, we investigated the cognitive control of ocular drifts with a letter discrimination task. The experiment was designed to reveal open-loop effects, i.e., cognitive oculomotor control driven by specific prior knowledge of the task, independent of incoming sensory information. Open-loop influences were isolated by randomly presenting pure noise fields (no letters) while subjects engaged in discriminating specific letter pairs. Our results show open-loop control of drift direction in human observers. [Display omitted] •Seemingly involuntary fixational eye movements are under cognitive influence•Specific task knowledge influences the dominant orientation of these ocular drifts•This influence is open-loop, as it can occur in the absence of visual information•Cognitive drift modulations can predict the specific task with above-chance accuracy Task demands are known to direct gaze to informative locations. Lin et al. show that task also modulates tiny, seemingly involuntary eye movements present during fixation, even when no visual information is present. Cognitive modulation of drift is of particular interest because it reveals a new aspect of cortical/brainstem functional interaction.